EFFECT OF METAL FILAMENT WIRE CONTAINING KNITTING FABRICS ON ELECTROMAGNETIC SHIELDING EFFECTIVENESS (EMSE) - (:unkn) unknown (UNIV ZAGREB, FAC TEXTILE TECH, 2010)
The growth of the electronic industry and the widespread use of electronic equipment in communications, computations, automations, biomedicine, space, and other purposes have led to many electromagnetic interference (EMI) problems as systems operate in close proximity. In recent years, electromagnetic (EM) waves in the 1-10 GHz range are broadly used in wireless communication tools and local area networks. In the future, the usable range of EM waves will tend to shift further to higher frequency regions with the development of information technology as well as electronic devices. As a consequence, the seriousness of problems such as EMI of electronic devices and health issues is ever rising. This paper describes a study on the development of finest metal wires /cotton knitted fabrics for electromagnetic shielding applications. Yarns which are made of finest metal wires and cotton fibers were fabricated by using the ring spinning methods. Their knitted fabrics made from 7G fiat knitting machine were developed successfully. Using a coaxial transmission line holder set-up, the electromagnetic shielding effectiveness (EMSE) of various knitted fabrics was carried out in the frequency range from 30 kHz to 3000 MHz. The variations of EMSE with the knitted structures and thickness of finest metal wires and wire to the cotton fiber in the yarns are discussed.
Keywords: electromagnetic shielding; knitting; meta wire; core-spun yarns